Hospital security. A vision of multidimensional security - Figueroa Uribe, Augusto Flavio (2020)
The risks during the performance of work is an inherent situation to any human activity. Hospital Safety is defined as: “the condition that guarantees that the workers, patients, visitors, infrastructure and equipment within a health care center are free of risk or danger of accidents”. The construction of the prevention culture starts from the knowledge of the risks, the safety culture is directly related to the quality of care of the service provided, which is why these terms are of special interest in health institutions. Talking about comprehensive risk management, either, involves determining all the risks that could cause considerable damage to these systems, given by the interaction of three factors, the presence of a threat, the existence of vulnerabilities and the time they are exposed to. Thus we can distinguish that hospital safety must be an internal policy of every health institution and that it can be divided into three main axes: 1. Patient safety, 2. Comprehensive risk management for major emergencies and disasters, 3. Internal safety and external to violence.